Identification of 315 genes essential for early zebrafish development - Amsterdam, Adam (National Academy of Sciences, 2004)
We completed a large insertional mutagenesis screen in zebrafish to identify genes essential for embryonic and early larval development. We isolated 525 mutants, representing lesions in ≈390 different genes, and we cloned the majority of these. Here we describe 315 mutants and the corresponding genes. Our data suggest that there are roughly 1,400 embryonic-essential genes in the fish. Thus, we have mutations in ≈25% of these genes and have cloned ≈22% of them. Re-screens of our collection to identify mutants with specific developmental defects suggest that ≈50 genes are essential for the development of some individual organs or cell types. Seventy-two percent of the embryonic-essential fish genes have homologues in yeast, 93% have homologues in invertebrates (fly or worm), and 99% have homologues in human. Yeast and worm orthologues of genes that are essential for early zebrafish development have a strong tendency to be essential for viability in yeast and for embryonic development in the worm. Thus, the trait of being a genetically essential gene is conserved in evolution. This mutant collection should be a valuable resource for diverse studies of cell and developmental biology.